2016
DOI: 10.3390/rs8050406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sentinel-1 Radiometric Stability and Quality for Land Surface Applications

Abstract: Abstract:Land monitoring using temporal series of Synthetic Aperture Radar (SAR) images requires radiometrically well calibrated sensors. In this paper, the radiometric stability of the new SAR Sentinel-1A "S-1A" sensor was first assessed by analyzing temporal variations of the backscattering coefficient (σ˝) returned from invariant targets. Second, the radiometric level of invariant targets was compared from S-1A and Radarsat-2 "RS-2" data. The results show three stable sub-time series of S-1A data. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 4 publications
3
38
0
Order By: Relevance
“…In addition, the soil contribution was simulated using the IEM modified by Baghdadi et al [15,17]. The results showed that the parameterized WCM simulates the backscattering coefficients in the VV and VH polarizations with an accuracy (Root Mean Square Error "RMSE") of approximately 1.4 dB (R 2 approximately 0.60), which is close to the S1 measurement accuracy [51,52].…”
Section: Radar Backscattering Modelmentioning
confidence: 90%
“…In addition, the soil contribution was simulated using the IEM modified by Baghdadi et al [15,17]. The results showed that the parameterized WCM simulates the backscattering coefficients in the VV and VH polarizations with an accuracy (Root Mean Square Error "RMSE") of approximately 1.4 dB (R 2 approximately 0.60), which is close to the S1 measurement accuracy [51,52].…”
Section: Radar Backscattering Modelmentioning
confidence: 90%
“…The correlation coefficient R2 is equal to 0.55 for VV and 0.63 for VH with RMSE (Root Mean Square Error) on the predicted backscattering coefficients of 1.55 dB in VV and 1.30 dB in VH. The RMSE obtained on the WCM predictions close to 1.5 dB are slightly higher than the Sentinel-1 precision [32,33]. Indeed, the radiometric accuracy for all measurement modes of Sentinel-1 is within 1 dB (3σ) and its sensitivity expressed by the noise equivalent sigma naught is −22 dB or higher [32].…”
Section: Water Cloud Model Validationmentioning
confidence: 93%
“…Both Miranda [57], and El Hajj et al [58] reported positive Sentinel-1A antenna gain biases between 19 March 2015 and 25 November 2015. Hence, all backscatter values within that timespan were corrected.…”
Section: Gtc Images γmentioning
confidence: 99%